The Theft: An Analysis of Moral Agency - Elfstrom, Gerard (Conatus - Journal of Philosophy, 2020)
Adam and Eve’s theft marks the beginning of the human career as moral agents.   This article will examine the assumptions underlying the notion of moral agency from the perspective of three unremarkable human beings who found themselves in situations of moral difficulty.  The article will conclude that these three people could not have acted differently than they did.  It will conclude that it is unreasonable to assume that ordinary human beings will inevitably possess the resources to address difficult moral decisions.